2022
DOI: 10.18176/jiaci.0854
|View full text |Cite
|
Sign up to set email alerts
|

Anaphylaxis: Mediators, Biomarkers, and Microenvironments

Abstract: The life-threating nature of the anaphylactic reactions promotes a growing interest to discover new biomarkers that could support their better diagnosis and prevention. However, both the clinical features and the etiopathology of anaphylaxis are very diverse, hindering the elucidation of valuable molecular indicators of disease. Most studies of anaphylaxis have focused on the immune system. Precisely, anaphylactic reactions are characterized primarily by IgE-mediated activation of mast cells and basophils and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 209 publications
1
8
0
Order By: Relevance
“…However, other IgE-independent molecular processes and cells are involved in this pathological event ( 8 ). Overall, there is a release of mediators that gives rise to signs and symptoms of anaphylaxis ( 9 ). Among them, the cutaneous ones are the most frequent, although the respiratory and cardiovascular systems mark the development of the most severe cases ( 10 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, other IgE-independent molecular processes and cells are involved in this pathological event ( 8 ). Overall, there is a release of mediators that gives rise to signs and symptoms of anaphylaxis ( 9 ). Among them, the cutaneous ones are the most frequent, although the respiratory and cardiovascular systems mark the development of the most severe cases ( 10 ).…”
Section: Introductionmentioning
confidence: 99%
“…The life-threatening nature of anaphylaxis fosters a growing interest in the improvement of its clinical management, as well as in the finding of new molecular markers that allows an accurate diagnosis of this pathological event. However, for this purpose, it is necessary to simultaneously increase the molecular knowledge underlying the clinical reaction ( 13 ). Precisely, circulating serum sncRNAs are emerging agents that have been described as non-invasive biomarkers and as messengers in the pathophysiology of different diseases ( 25 , 26 ).…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, their molecular function has not been fully defined yet ( 40 , 41 ). Nevertheless, one study showed that YRFs regulate cell death and inflammation in monocytes/macrophages ( 42 ), which are relevant cells for the development of anaphylaxis, especially in non-IgE-mediated reactions ( 12 , 13 ). Therefore, the increase of YRFs could be related to a modulation of monocyte and macrophage activation in anaphylaxis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is plenty of evidence for the importance of extracellular vesicles in pathological states. From cancer interaction with the immune system ( Pelissier Vatter et al, 2021 ) to cancer resistance to therapy ( Palazzolo et al, 2022 ), from cardiovascular disease ( de Abreu et al, 2020 ) to anaphylaxis ( Fernández-Bravo et al, 2022 ), the EV role in pathogenesis and its potential use as biomarker have been well characterized, albeit there are still many questions to answer. However, EVs role in normal physiology or cellular and tissue homeostasis presents multiple pending questions.…”
Section: Evs In Normal Homeostasismentioning
confidence: 99%